Cassava Price Dynamics in Lampung Province: Economic and Social Factors That Influence - Naqiya, Alfina Zsazsa; Rozi, Fakhrur (Universitas Indonesia Mandiri, 2025)
Cassava prices in Lampung, one of the largest cassava producers in Indonesia, experience fluctuations influenced by various economic and social factors. This study aims to identify and analyze the factors that influence the dynamics of cassava prices in Lampung province. The method used in this study is descriptive analysis with qualitative and quantitative approaches. The results of the study indicate that the main factors influencing cassava prices in Lampung include weather conditions, government policies related to prices and subsidies, transportation costs, and domestic and export market demand. Social factors, such as the socio-economic conditions of farmers and the relationship between traders and consumers also play an important role in determining prices. This study provides recommendations on policies that can be implemented to reduce price fluctuations and improve the welfare of cassava farmers in Lampung.